Tweet ye, tweet ye a case study on the Twitter account of the Metropolitan Manila Development Authority - Pascua, Erika Dela Cruz (2012)
"This research is a case study of the Twitter account of the Metropolitan Manila Development Authority or the MMDA. It aimed to determine the motivations behind the account, its history and its daily operations. The researcher conducted interviews with the team and its head, content analysis of the agency's tweets and a survey of followers for this case study. The researcher found out through the interviews that the Twitter account was a replacement for the other media the agency used, which were too expensive to maintain-TV and radio. The interviews also gave the researcher and inside view of the day-to-day operations of the 24-hour service. Through the data analysis the researcher found that of 4599 of the 7678 tweets of the agency are tweets about the traffic situation in the metro. That accounts for roughly 59% of all the agency's tweets. The survey fielded the result that not all the followers of the MMDA on Twitter interact with the agency through that medium. In conclusion, the researcher found that twitter is a useful and effective information dissemination tool for the MMDA. It is recommended that the agency begin backing up its tweets through online databases."